Sistem Pendukung Keputusan Menentukan Siswa Berprestasi menggunakan Metode Weighted Product dan Simple Additive Weighting (Studi Kasus : SMPN 2 Bululawang Kabupaten Malang) - Mukhlis Anshori Witanto; Edy Santoso; Suprapto Suprapto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The number of students as well as various levels of ability and strengths in different aspects of behavior, academic values ​​and non-academic values, so that based on the conditions that emerge an effort to find out students have superior achievements. The selection of high achieving students in SMP Negeri 2 Bululawang tends to be use the academic scores of the nasional exam, because the decisions taken only use the academic scores of the national exam, so it is not fair to make high performance student decisions that are seen in one criterion. In carrying out a decision support system for determining these high achieving students using the Weighted Product (WP) and Simple Addictive Weighting (SAW) methods. This system uses several criteria used for the selection of high-achieving students including, the average report card grades from grade 7 to grade 9, school exam scores, attendance attendance values, and extracurricular grades. The test results obtained an accuracy of 40%, because the school only determines from one aspect only.